Influence of Sex and Level on Marathon Pacing Strategy. Insights from the New York City Race - Santos-Lozano, A.; Collado, P. S.; Foster, C.; Lucia, A.; Garatachea, N. (International Journal of Sports Medicine, 2014)
Different pacing profiles have been identified in the literature for endurance sporting events: the ‘positive’, ‘negative’, ‘even’, ‘parabolic shaped’ and ‘variable pacing’. Most studies have focused on competitive or elite athletes (including winners) without considering more recreational runners, for many of whom the primary goal is simply to finish the event. The major city marathons provide a large heterogeneous sample to compare the pacing profiles of competitive vs. recreational runners, and thus to understand pacing more broadly. A total of 190 228 New York finishers’ (69 316 women) marathon times (from 2006 to 2011) were assessed. Although all runners developed a positive pace profile, a lower variability of speed through the race was found in the top runners (coefficient of variation (CV) for speed during 5-km splits: 7.8% (men) and 6.6% (women)) compared with the less successful runners (CV ranging from 8.3 to 14.4%). Both men and women try to maintain an even pace profile along the marathon course, partly by avoiding an excessively fast start that might result in a pronounced decrease in the speed in the second half of the race.
Keywords: aerobic; exercise performance; sport physiology; marathon; pacing